Triggering Factors that Reinforce or Change EFL Preservice Teachers' Beliefs during the Practicum - Abel Andrés Periñan-Morales; John Jairo Viáfara-González; José Alexander Arcila-Valencia (Universidad Nacional de Colombia, 2022)
This exploratory case study seeks to examine the role that specific factors exert on the evolution of beliefs in preservice English teachers during their final teaching practicum. Data were collected through reflections, interviews, focus groups, and observations. The findings revealed that three groups of factors affect belief evolution during the practicum: participant subjectivity, contextual circumstances, and university support community. Subjectivities encompassed preservice teachers' fears, reactions to real-life teaching challenges, and enthusiasm to become teachers. Contextual circumstances incorporated classroom circumstances and cooperating teachers. The university support community concerned their peers and the university tutor. Implications discuss the relevance of curricular and reflective agendas that enrich the education of future teachers through beliefs exploration.